The Effects Of Up Selling And Gastrodiplomacy On The Consumer Purchasing Power Of Japanese Halal Food Products Case Study Food Retail Sushi Tei In North Sumatera - Gusdini, Wan melia; Lestari Nasution, Annio Indah; Imsar, Imsar (Universitas Ibn Khladun Bogor, 2023)
Understanding different cultures from other countries can be done through cuisine that can be used as a tool to promote international relations and offer someone to visit the place of such international food or buy cultural food sold. This study aims to: 1) Analyze the effect of up selling on the consumer purchasing power of Japanese halal food products at Sushi Tei food retail in North Sumatra. 2) Analyze the effect of gastrodiplomacy on the consumer purchasing power of Japanese halal food products at Sushi Tei food retail in North Sumatra. 3) Analyze the effect of up selling and gastrodiplomacy on the consumer purchasing power of Japanese halal food products at Sushi Tei food retail in North Sumatra. This study uses a quantitative descriptive research method using an associative research strategy. The sampling technique used non-probability and purposive sampling techniques with a total sample of 75 respondents. In this study, the SPSS 25 program was used for data processing. The results of the study show that up selling and gastrodiplomacy significantly affect the purchasing power of consumers of Japanese halal food products at Sushi Tei, North Sumatra.